Hg2+-Quinalphos Complexes: Characterized by 1H and 31P NMR - Abdelhamid Esbata; Erwin Buncel; Gary VanLoon (AlQalam Journal of Medical and Applied Sciences, 2021)
Since Hg2+ has catalyzed the hydrolysis of quinalphos and ESI-MS detects species in the gas phase [1], 1H and 31P NMR studies were carried out in this work in order to verify whether the metal ions bind to the quinalphos (Q) and its products in solution. The NMR results show clearly that binding between Hg2+ and quinalphos occurs primarily through the S atom. However, small 1H shifts suggest weaker interaction through N. This support strongly that Hg2+ may form a six membered ring with quinalphos and that this complex enhancing the hydrolysis rates.